A Thematic and Stylistic Analysis of Christianised Traditional Anlo Songs: A Case Study of St. Mary’s Roman Catholic Church, Hatorgodo. - Agbezorlie, K. P. (University of Ghana, 2014)
This thesis attempts a thematic and stylistic analysis of what I term ―Christianised Traditional Anlo Songs (CTAS)‖. These songs are traditional Anlo songs that have been adapted and are being used in Christian worship in recent times without discrimination. They were hitherto termed ‗evil‘ and ‗pagan‘ and were consequently banned in Churches prior to the formation of Pentecostal movements and churches in Ghana in the late 1970s. The question then is why are they being embraced now? The Christianised Traditional Anlo Songs (CTAS) were recorded, transcribed, translated and analysed against the backdrop of Anlo world views and Roman Catholic beliefs and practices. These songs have been thematically classified under four themes: (i) salvation (ii) futility of idol worship (iii) freedom in Christ and (iv) goodness /kindness of God. CTAS depict Christianity as the most ideal religion and are used to ridicule and attack African traditional religious practices such as afã divination and idol worship and their functionaries. In condemning these ―so called‖ pagan practices, the Catholic Church appears to open itself to criticisms as some of these practices are prominent in the CTAS and some doctrines of the church. I have investigated the use of imagery, symbolism, allusion, hyperbole, repetition and parallelism as tools for communication in the CTAS to their (Christians‘) prospective converts. In summary, it has been found that these stylistic techniques have Biblical leanings. Three levels of adaptation of CTAS have been identified as (i) lexical adaptation/substitution (ii) tune adaptation and (iii) drum adaptation. These levels of adaptation can be mapped onto the developmental stages 1, 2, and 3 of the CTAS. Most of the traditional Anlo songs (TAS) which are in the corpus whose equivalents are the CTAS have been found to be related to cults such as afã and social dances like kenka. In the CTAS, everyday language is used.
Thesis, (MPhil)- University of Ghana, 2014
Keywords: Anlo songs; Christian worship songs; Thematic and Stylistic analysis; Roman Catholic Church